A study on the pattern of tobacco use and its implications on the health of patients, attending Karnataka Institute of Medical Sciences, Hubballi - K., Pratibha Rao; Bant, D. D. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco use plays an important role in the causation of various health issues. Although numerous efforts are being done to increase the awareness among people regarding its proven role in disease causation, it remains as one of the important public health issues in our country. Information regarding the tobacco habits in patients and its relation to their health status is scarce. Thus with this objectives, the present study was conducted in Karnataka Institute of Medical Sciences, Hubballi. Methods: A cross-sectional, questionnaire based study was conducted among the outpatients of Karnataka Institute of Medical Sciences during July 2017. Information was collected regarding the form of tobacco used, duration of use and their health problems. Statistical analysis was carried out using descriptive statistics and chi-square tests using Statistical Package for Social Sciences (SPSS) version 21. Results: The tobacco use was reported among 93 patients (44.3%). Among the tobacco users, majority of them were males (80.6%), and in the age group of 31-60 years (67.7%). The smokeless form of tobacco was the most common form used in both gender (44%). Health issues related to heart, respiratory system and oral cavity was seen more among the tobacco users than non-users. Conclusions: The study concludes that tobacco consumption among patients attending KIMS Hospital is high, which clearly has a negative impact on their health. Health care institutions also have a major role in imparting health education and motivating their tobacco addict patients to quit the habit.